Knowledge economies : organization, location and innovation - Dolfsma, Wilfred (London ; New York : Routledge, 2008)
This book discusses knowledge economies, innovations and provide a range of theoretical insights from different perspective.
Introduction -- Knowledge and learning -- Creating knowledge : transfer, exchange and gifts -- Development of economic knowledge : paradigms and new ideas -- Knowledge exchange in networks : within-firm analysis -- Knowledge exchange between firms : economic geography of high-tech firms -- The knowledge base of an economy : what contributes to its entropy? -- A dynamic welfare perspective for the knowledge economy -- Concluding remarks.
Includes bibliographical references (p. [129]-151) and index.
nif 22/04/13
Loans
Keywords: Knowledge management; Organizational learning; Intellectual capital; Communication in organizations; Communities of practice